Potassium Dichromate Detection: Carbon Quantum Dot-based Fluorescent “Turn-Off” Nanoprobe Design - Priti Sharma; Sopan Nangare; Rahul Tade; Pravin Patil; Sanjkumar Bari; Dipak Patil (Nano Biomedicine and Engineering)
The occurrence of potassium dichromate in food poses serious health risks, including cancer and skin-related issues. Conventional sensing methods, known for their poor sensitivity, low selectivity, and high costs, highlight the need for improved detection methods. This study addresses this gap by exploring the use of carbon quantum dots (CQDs) synthesized from Tamarindus indica leaves through an eco-friendly hydrothermal approach for the detection of potassium dichromate. Briefly, the synthesized CQDs underwent spectroscopic characterizations. Following this, the CQDs-based sensor was assessed for key analytical parameters such as sensitivity, selectivity, and the analysis of spiked milk samples to detect potassium dichromate. As a result, analyses of particle size and zeta potential confirmed the formation of stable, nanosized CQDs. The introduction of potassium dichromate led to the quenching of CQDs’ fluorescence, likely attributed to mechanisms such as the inner filter effect (IFE) and fluorescence resonance energy transfer (FRET). The established linearity range and limit of detection were determined to be 50–500 and 148 μmol/L, respectively. Confirmation of the sensor’s practicality was obtained through the analysis of spiked samples, suggesting that CQDs could potentially serve as a viable alternative for detecting potassium dichromate in milk samples in the future.